AKTIVITAS MEDIA SOSIAL INSTAGRAM SEBAGAI PENENTU KEPUTUSAN PEMBELIAN PAKAIAN BRAND VICKY SVPIT - Kanaya Safitri; Uuh Sukaesih; Miswan Miswan (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
The study was conducted with three objectives: 1). Identifying follower activity on the Vicky Svpit clothing brand Instagram account, 2). Evaluating consumer purchasing decisions for Vicky Svpit clothing brand products, 3). Determine the influence of Instagram social media activity on purchasing decisions for Vicky Svpit clothing brand. The research method applied involved the use of questionnaires distributed to 90 respondents. The respondent criteria were active Instagram users who had previously purchased the product. For data analysis, a quantitative descriptive analysis approach and simple linear regression analysis were used. The results of the study revealed that follower activity on the Vicky Svpit clothing brand Instagram account (@vicky.svpit) was classified as active and interesting, in addition, the purchase decision for the brand's clothing showed high results. Furthermore, the results of the analysis showed a positive and significant influence of @vicky.svpit Instagram social media activity on purchasing decisions for Vicky Svpit clothing products.